Where to Find Leucine in Food and How to Feed Elderly With Sarcopenia in Order to Counteract Loss of Muscle Mass: Practical Advice - Rondanelli, Mariangela; Nichetti, Mara; Peroni, Gabriella; Faliva, Milena Anna; Naso, Maurizio; Gasparri, Clara; Perna, Simone; Oberto, Letizia; Di Paolo, Enrica; Riva, Antonella; Petrangolini, Giovanna; Guerreschi, Giulia; et al. (Frontiers in Nutrition, 2021)
The term sarcopenia refers to the loss of skeletal muscle mass and strength that generally occurs during aging. The interventions that have proved most effective in reducing the severity and preventing the worsening of sarcopenia include physical exercise, especially resistance, and the administration of dietary supplements in association with a targeted diet; nutritional intervention is the main therapeutic approach for elderly people, since they are very often sedentary (also due to possible disabilities). Among the various nutrients, high biological value proteins and leucine are of particular interest for their demonstrated effects on the health of skeletal muscle. The intake of food containing proteins and leucine during meals stimulates muscle protein synthesis. Lower blood levels of leucine were associated with lower values of the skeletal muscle index, grip strength and performance. The international guidelines recommended that a leucine intake of 3 g at three main meals together with 25-30 g of protein is the goal to be achieved to counteract loss of lean mass in elderly. Food composition databases rarely show the amounts of leucine contained in foods and therefore it becomes difficult to build a diet that follows these guidelines. A table was therefore created for the first time in the literature to collect all the foods richest in leucine, thanks to the union of the most important Italian food databases. Moreover, in order to implement a diet that follows the right recommendations, another tables shows nutritional composition of breakfast, lunch and dinner (that each provide 3 grams of leucine and 25 grams of protein) for seven days.